Application of STEAM in PBL to Improve Creativity and Science Learning Outcomes: Case Study of Learning at SD Inpres Tanamodindi Palu - Muh. Rizal; Sri Muliani; Sarintan N Kaharu; Ijirana; Vivien Marvina; Elyas Djufri; Ika Kartika (Postgraduate, University of Mataram, 2025)
The purpose of this study is to explore the implementation of Science, Technology, Engineering, Arts, and Mathematics (STEAM) within a problem-based learning (PBL) approach to enhance students' creativity and learning outcomes in science subjects at SD Inpres Tanamodindi. The research was conducted in Grade V of SD Inpres 1 Tanamodindi Palu, where students exhibit diverse academic abilities. Following the research design proposed by Kemmis and McTaggart (2013) and Zhong, Y. (2024), the study was carried out in two cycles. Data collection methods included observations, interviews, field notes, and learning outcome assessments. The findings reveal that integrating the STEAM approach into the PBL model at SD Inpres Tanamodindi led to an improvement in learning outcomes, rising from 64.65 in the first cycle to 71.77 in the second cycle. Additionally, students' creativity in solving science-related problems improved, progressing from the